IMPROVING LISTENING SKILLS IN ENGLISH LEARNERS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the significance of listening skills in the process of English language acquisition and identifies major challenges that learners commonly face. It provides a comprehensive overview of pedagogical strategies, technological tools, and learner-centered practices that promote listening proficiency. Drawing on contemporary research in applied linguistics, second-language acquisition (SLA), and educational psychology, the paper evaluates methods such as extensive and intensive listening, shadowing, multimodal input, task-based learning, and accent exposure. The findings highlight that effective listening development requires a combination of cognitive, social, and environmental support systems. The article concludes with implications for teachers, students, and curriculum designers, while emphasizing the need for consistent practice, varied input, and metacognitive awareness.